Twist Solid GMS560 v0.6.1 panel of normals - Almlöf, Jonas (Uppsala University, 2023)
The data included here are part of a collection of different types of reference data used in the bioinformatic analysis pipeline called Twist Solid GMS560. The pipeline is based on the Hydra-genetics framework and analyses NGS short read data from the GMS560 Twist panel which is used on solid cancer samples.

The data in this specific item include panel of normals and artifact filer files generated for the Twist GMS560 panel. Panel of normals and artifacts are specific to panel used and sequencing machine. Programs using these files include MSIsensor-Pro, GATK CNV, CNVkit, SVDB, PureCN, and small variant filtering.
Keywords: Other health sciences not elsewhere classified; Medical and Health Sciences; Medicin och hälsovetenskap; Other Health Sciences; Annan hälsovetenskap